Retinal manifestations after Dengue fever. A case report - Raisa Ivis Beltrán Saínz; Raisa Hernández Baguer; Loida Mevis Savón George (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: Dengue is an acute viral infection, caused by a virus of flaviviridae family that is transmitted by the Aedes Aegypti mosquito sting. Ocular manifestations associated to this illness have been described such as maculopathy, retinal hemorrhages, optic neuritis, retinitis and vasculitis, although they are not frequent. Objective: To present a case that is not frequently reported in own context. Case presentation: 58-year-old male patient that suffered from dengue and 1 month after that he began having blurred vision in both eyes. In the ophthalmic examination, it was detected that he had macular hemorrhages and exudates in some quadrants of both eyes. He was treated with systemic antiinflammatories for 2 months. There was an improvement of his initial symptoms and the clinical features of the ocular fundus with this treatment. Conclusions:  Dengue is an illness that has not only a systemic impact but also causes ophthalmic damage that we should consider. The clinical manifestations, the retinophoto and the optical coherence tomography (OCT) were considerably useful for the follow-up of the retinal alterations found post-dengue. Steroids were used successfully for the treatment of this case.    Keywords: Dengue, post-dengue maculopathy, post-dengue retinal hemorrhages, optic neuritis.